2020
DOI: 10.1155/2020/4274037
|View full text |Cite
|
Sign up to set email alerts
|

Intracorneal Stromal Ring Can Affect the Biomechanics of Ectatic Cornea

Abstract: Purpose. The biomechanical properties of ecstatic cornea undergo changes. This study evaluates the biomechanical changes of ecstatic cornea after implantation of two types of intracorneal stromal ring (ICR). Methods. For doing this prospective cross-sectional study, 32 patients with keratoconus (KCN) were randomly divided into two 16-member groups (group I: MyoRing, group II: KeraRing). The main inclusion criteria were transparent cornea with no scar in the central part, corneal thickness >450 µ in the inci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 18 publications
2
8
0
Order By: Relevance
“…Our results were similar to the study done by 54.38±1.17 to 47.39±0.62D [13]. has some stabilizing influence upon corneal bio-mechanics, while this impacts continue only about 6-mths, and its role is mostly for correcting the refraction and progress vision [14], which isn't sufficient to stop the development of KC, which needs CXL, that hardens the then weak and flaccid corneal stroma [15]. Managements of progressive corneal ectasia is challenging for any corneal surgeon.…”
Section: Discussionsupporting
confidence: 91%
“…Our results were similar to the study done by 54.38±1.17 to 47.39±0.62D [13]. has some stabilizing influence upon corneal bio-mechanics, while this impacts continue only about 6-mths, and its role is mostly for correcting the refraction and progress vision [14], which isn't sufficient to stop the development of KC, which needs CXL, that hardens the then weak and flaccid corneal stroma [15]. Managements of progressive corneal ectasia is challenging for any corneal surgeon.…”
Section: Discussionsupporting
confidence: 91%
“…It can be explained that, regarding the inter corneal layer adhesion with the tunnel incision method in contrast to pocket cut, the cornea was less affected by the external loading and, consequently, demonstrated higher stiffness against the air-puff by exhibiting less apical displacement and a flatter central surface (greater HCR). In this context, a clinical research [36] of MyoRing and KeraRings effects on corneal biomechanics in the first year after ICRS implantation also confirms the present numerical findings. The clinical study suggested that the effect of lamellar cut in redistributing the collagen lamellae arrangement in the cornea leads to a significant difference in the highest radius of curvature and corneal flattening result, where the HCR factor can be used to assess the progression of corneal ectasia after ring implantation.…”
Section: Effect Of Icrs On Corneal Deformations and Shape Regularization (Fem Validation)supporting
confidence: 88%
“…Biomechanical considerations ascribing higher stabilization of the corneal by continuous rather than interrupted segments favor ICCR implantation. 10 , 11 This is particularly relevant since some publications report of regression to baseline of CDVA improvements 12 months after ICRS implantation, particularly in progressive KC. 12 , 26 , 28–31 …”
Section: Discussionmentioning
confidence: 99%
“…All steps have been described in previous publications. 11,13 Main Outcome Measures Our primary outcome measures were the improvement of uncorrected distance visual acuity (UDVA) and CDVA as measured in logMAR chart lines. UDVA and best spectacle-CDVA were measured using a decimal scale and transformed into logMAR values for statistical analysis.…”
Section: Dovepressmentioning
confidence: 99%
See 1 more Smart Citation